Cervical smears and human papillomavirus typing in sex workers. Issue 2 (30th March 2004) - Mak, R; Van Renterghem, L; Cuvelier, C
Abstract : Objectives: Sex workers are at increased risk for sexually transmitted infections (STI), human papillomavirus (HPV) and hence cervical cancer. In Belgium screening for cervical cancer starts at the age of 25, and is at 3 yearly intervals. The aim of this study is to assess risks for abnormal cervical smears and HPV in sex workers and decide whether the current screening policy is sufficient for them. Methods: In an outreach programme for sex workers results of 653 smears sampled between 1992 and 2001 were analysed, and compared to a control group matched for age from the general population in 2001. Separately, 99 consecutive samples were typed for HPV and compared to an equal control group, matched for age. Smears and typing were performed according to current techniques. Results: In the sex worker group 2.6% were diagnosed with atypical glandular cells of undetermined significance (AGUS)/atypical squamous cells of undetermined significance (ASCUS), 15.6% with low grade squamous intraepithelial lesion (LSIL), and 2.9% with high grade squamous intraepithelial lesion (HSIL), and in the control group results were 1.4%, 2.9% (p<0.001) and 0.6% (p<0.001) respectively. When considering only those under 25 years, 24.4% should have further follow up. Of the sex workers, 77.4% were positive for one or more types of HPV (55.9% for high risk HPV), in comparison with 27.6% of the control group (14.3% for high risk HPV) (p<0.001). In high risk HPV samples more LSIL and HSIL were found. Conclusion: Abnormal smears and high risk HPV were significantly more prevalent in sex workers than in controls. Current screening policy would miss many sex workers with an abnormal smear who should be referred for further follow up. It is proposed to screen sex workers when they enter prostitution regardless of their age.